Current advances in ischemic stroke management - Żyga, Justyna (Journal of Education, Health and Sport, 2022)
Stroke is one of the leading causes of morbidity and mortality worldwide with 24.1 million new stroke cases in 2017 and 700,000 more stroke-related deaths, as compared to 2016. Although some patients recover after a stroke, the significant majority continue to have numerous health problems resulting in substantial decrease of life quality. This article reviews the evaluation and the current advances in the management of acute ischemic stroke, starting in the prehospital setting followed by stroke hospital management. Conclusions: Appropriate treatment of ischemic stroke is essential in the reduction of mortality and morbidity. Therapeutic methods have greatly expanded beyond the utility of intravenous thrombolysis, with more advanced and complex techniques. Mechanical thrombectomy has revolutionised the management through the clot retrieval techniques improving patient outcomes. Appropriate application of the available treatment methods is crucial to optimising outcomes of patients with stroke, starting from pre-hospital accurate assessment. High-quality care of patients with ischemic stroke requires efficient cooperation of multidisciplinary medical staff.